Polarization, purpose and profit - Daniel Bernardo Soares Ferreira; Radoslawa Nikolowa (Queen Mary University of London, School of Economics and Finance, 2024)
We present a model in which firms compete for workers who have a taste for a nonpecuniary job attribute, such as purpose, sustainability, ES/CSR, or working conditions. Firms can invest in flexible production technologies that allow them to create jobs with different levels of the desirable job attribute. In a competitive equilibrium, flexible firms become polarized and cater to workers with extreme preferences for the job attribute. Firm polarization increases with technological progress and industry concentration. More polarized sectors have higher profits, lower average wages, and a lower labor share of value added. Traditional investors prefer to buy shares in polarized sectors, while socially responsible investors prefer to invest in less polarized sectors. Firms in more polarized sectors are more valuable and have higher stock returns than firms in less polarized sectors.
Keywords: 330; Labor Markets; Job Design; Compensating Differentials; Socially Responsible Investment; Polarization